Efforts to Improve Learning Outcomes of Dribbling in Learning Football Games Through the Application of Learning Interaction Teaching Styles SMP Muhammadiyah 57 Medan - Azimah, Azimah; Ramadan, Ramadan (Journal of Physical Education Innovation, 2024)
This study aims to see the results of students' dribbling learning in sports lessons with a learning model of learning interaction teaching style at SMP Muhammadiyah 57 Medan in the 2020/2021 Academic Year. This research includes classroom action research. The subject of this research was taken at SMP Muhammadiyah 57 Medan in the 2020/2021 academic year with a total of 20 students consisting of 17 students and 3 students. At the beginning of the KBM learning outcomes test (Pretest), with an average data of 63 with a passing percentage of 30%, it shows that the ability to dribble by students is still low. Then continued with KBM using the learning model of learning interaction teaching style, at the end of the first KBM and the second KBM, a ball dribbling learning outcome test was conducted. Cycle I obtained an average grade of 71.3, the percentage of graduation was 70% of class students whose grades were above the KKM and experienced an increase. in Cycle II with an average grade of 86.2 with a passing percentage of 86% of class students whose grades are above the KKM. From these data it can be concluded that the value of students' dribbling learning outcomes has increased from before being treated with the teaching style learning model of learning interaction to the first cycle and also increased in the second cycle. The application of the teaching style learning model of learning interactions during KBM students are very happy, and very enthusiastic. However, there are still limitations in the research conducted at SMP Muhammadiyah 57 Medan for the 2020/2021 Academic Year, namely the material discussed in this study is "dribbling", this does not guarantee that other materials will experience higher learning outcomes. same and further research should be carried out..